sPring 2000 : Jong Talent in Antwerpen. - Donkers, Danny; Meurrens, Luc; Paulus, Camille; Vanderschrieck, Katleen; Vanhoof, Sofie; Walgrave, Jan (Antwerpen : Provincie Antwerpen, 2000)
Baeken, Jeroen ; Denys, Ward ; De Ranter, Christophe ; Derdyn, Maaike ; Donkers, Guy ; Fleischer, Silke ; Redjaian, Haleh ; Steenbergen, Frederik ; Tosseyn, Tom ; Vandeperre, Jo ; Vandeplas, Aline ; Vanderschrieck, Katleen ; Van Grimbergen, Ward ; Vanhoof, Sofie
biog. per kunstenaar
Nederlands
sPring 2000 : Jong talent in Antwerpen, Koningin Fabiolazaal, Antwerpen, 20 april - 21 mei 2000
boek
Keywords: Antwerpen